The challenge of interoperability: Model-based integration for automotive control software - Huafeng Yu; Joshi, Prachi; Talpin, Jean-Pierre; Shukla, Sandeep; Shiraishi, Shinichi (Proceedings - ACM IEEE Design Automation Conference, 2015)
Model-Based Engineering (MBE) is a promising approach to cope with the challenges of designing the next-generation automotive systems. The increasing complexity of automotive electronics, the platform, distributed real-time embedded software, and the need for continuous evolution from one generation to the next has necessitated highly productive design approaches. However, heterogeneity, interoperability, and the lack of formal semantic underpinning in modeling, integration, validation and optimization make design automation a big challenge, which becomes a hindrance to the wider application of MBE in the industry. This paper briefly presents the interoperability challenges in the context of MBE and summarizes our current contribution to address these challenges with regard to automotive control software systems. A novel model-based formal integration framework is being developed to enable architecture modeling, timing specification, formal semantics, design by contract and optimization in the system-level design. The main advantages of the proposed approach include its pervasive use of formal methods, architecture analysis and design language (AADL) and associated tools, a novel timing annex for AADL with an expressive timing relationship language, a formal contract language to express component-level requirements and validation of component integration, and the resulting high assurance system delivery.